Analysis of possible influence of conjugated linoleic acid on growth performance and losses of piglets - Hadaš, Z; Čechová, M; Nevrkla, P (Reproduction in domestic animals, 2015)
The aim of this work was to evaluate the effect of supplementing the feed ration for lactating sows with the conjugated linoleic acid (CLA) on the growth performance and losses of piglets from birth to weaning. The monitoring comprised 20 litters in control and 20 litters in experimental group of Czech Large White × Czech Landrace hybrid combination sows. The control group was given a standard feed mixture for lactating sows, and experimental group was fed with the feed mixture supplemented with 2% of CLA, from the day of farrowing to the weaning of piglets, that is for the time of 28 days. The results of the experiment indicate the significantly better parameters of the numbers of reared piglets in the experimental group and the related lower level of losses of piglets from birth to weaning (p < 0.01). However, the feed mixture for lactating sows enriched in conjugated linoleic acid had no significant effect on the growth performance of piglets from birth to weaning (p > 0.05). Sows in the experimental group showed earlier onset of post-partal oestrus after weaning of piglets (p < 0.05). These findings demonstrate that the supplementation of diet for lactating sows with CLA can improve survival of piglets from birth to weaning and shortening of weaning-to-oestrous interval in sows.
Keywords: Animals; novorozená zvířata; rozmnožování; Fertilization; Female; fertilizace; konjugované kyseliny linolové; ženské pohlaví; odstavení; Sus scrofa; Reproduction; laktace; Animal Feed; Dietary Supplements; Animals, Newborn; Linoleic Acids, Conjugated; kojená zvířata; estrus; Weaning; potravní doplňky; dieta; Animals, Suckling; Diet; fyziologie výživy zvířat; Estrus; Animal Nutritional Physiological Phenomena; krmivo pro zvířata; zvířata; Lactation